Psychobiotics, Novel Therapeutic Agents for the Psychiatric Disorders - Praveen Reddy P.; K. Sandhya; Aparna Srikantam (Novel Research in Microbiology Journal)
Various neurological disorders such as Parkinson’s disease, Alzheimer’s disease, autism spectrum disorder in young children, stress, anxiety etc., are afflicting the people all over the world. The pathophysiology of some of these disorders is not fully understood. Furthermore, the conventional therapies are not effective for all patients with psychiatric disorders. Hence, alternative therapeutic strategies/agents are much needed. Clinical researchers suggest that certain microorganisms (beneficial microorganisms/probiotics) could be substituted for conventional therapies and/ or can be used in combination with current drugs. Such beneficial microorganisms which can influence the central nervous system and cure the neurological complications are referred to as psychobiotics. In fact, the psychobiotics are the probiotic/ prebiotic agents which when present in the human gut region will not only improve the gut health but also influence the central nervous system via gut-brain axis, and counteract the symptoms of various neurological disorders. Till date, numerous probiotic bacteria and prebiotic compounds were identified and the majority of them are able to influence the nervous system. In various clinical trials on animal models and humans, it was proved that psychobiotics are effective in ameliorating the clinical symptoms of neurological disorders. Some of the researchers are employing psychobiotics in combination with traditional drugs for treatment of the psychiatric disorders. The aim of the current review is to investigate the concept of psychobiotics, detailing their mechanisms of action and discussing their potential applications in the treatment of certain psychiatric disorders. Subsequently, this study delineated the characteristics of psychobiotics and highlighted their impacts on the nervous system. Additionally, various psychobiotics utilized in the management of specific psychiatric conditions have been examined based on numerous clinical trials and experiments conducted on both animal models and human subjects.